P136 Management of patients with Inflammatory Bowel Disease and their outcome during the first wave of Covid-19 pandemics. (27th May 2021) - Viola, A; Giambò, F; Chiappetta, M F; Costantino, G; Pallio, S; Navarra, G; Alibrandi, A; Fries, W
Abstract: Background: The restrictions adopted in Italy during the phase I COVID-19 pandemics with a nationwide lockdown period, represented a challenge in the management of Patients with Inflammatory Bowel Disease (IBD) patients. The aim of the present study was to assess if, and how, a limited course of telemedicine did influence the clinical outcome in patients with Crohn's disease (CD) and Ulcerative Colitis (UC). Methods: IBD patients followed before March 8 th, 2020 were included and divided into 3 groups (Fig.1 ): group 1, patients on endovenous biologics (EV); group 2, patients on biologics administered subcutaneously (SC); and group 3, patients on conventional treatments (CT) at the start of lockdown. The primary outcome was to assess the occurrence of disease flare in the three groups since only the EV group received face-to-face visits during lockdown. As secondary outcome we assessed the number of control endoscopies performed and the start of new biologic therapies, compared with a reference period in 2019. Results: A total of 689 patients (CD: 369, UC 320) were included in the study (247 IV, 217 SC and 225 CT, respectively). Telemedicine was more frequently adopted in SC and CS, (p<0.001) both. Treatment delays or transitory stops were more frequent in EV (p<0.001), whereas there was a significantly greater need to change therapy (p= 0.038) and need for steroids (p = 0.008) in the SC group compared with EV (Tab.1 ). Concerning endoscopies, compared with the reference period in 2019 only 25% of scheduled endoscopies were performed. The only risk factor for disease flare during or shortly after lockdown was belonging to the patient groups subjected to telemedicine (SC and CT groups) (p < 0.001). Conclusion: Patients followed with a face-to-face approach instead of telemedicine, had a lower risk of disease flare during lockdown period. The impact of the important reduction of endoscopic assessments still needs to be assessed.